Sperm chromosome segregation of rob(4;16) and rob(4;16)inv(4) in the brown brocket deer (Mazama gouazoubira) - Galindo, D. J. [UNESP]; Vozdova, M.; Kubickova, S.; Cernohorska, H.; Bernegossi, A. M. [UNESP]; Kadlcikova, D.; Rubes, J.; Duarte, J. M.B. [UNESP] (Elsevier, 2021)
The genus Mazama stands out among the Neotropical deer due to their wide intra and interspecific karyotypic diversification, which is associated with an accentuated chromosomal fragility. There are reports of heterozygous Robertsonian translocation (RT) carriers in a free-range population of Mazama gouazoubira (brown brocket deer), as well as in captive animals of this and other species of the genus. To analyze possible negative impacts of heterozygous chromosome rearrangements on reproductive fitness of the carriers, we performed an analysis of sperm meiotic segregation in four brown brocket bucks, carriers of a rob(4;16), and compared the results with those of a normal buck. We established a reliable FISH and sperm-FISH protocol for the brown brocket deer using bovine (Bos taurus; diploid number, 2n = 60) whole chromosome painting (WCP) and BAC probes. Using BAC probes, we revealed the presence of a paracentric inversion (PAI) of the fused chromosome 4 in two of the four analyzed RT carriers. The mean frequency of normal/balanced sperm in the translocation carriers was significantly lower than in the normal buck (94.78% vs 98.40%). The mean value of total unbalanced spermatozoa was almost doubled in the RT/PAI carriers (6.68%) when compared to RT carriers (3.76%), but the difference was not statistically significant. This study demonstrated the efficiency of FISH with bovine WCP and BAC probes in the characterization of chromosome rearrangements and gametic segregation patterns in brown brocket deer. Our results indicate a low to moderate increase in the rates of unbalanced meiotic segregation products in brown brocket bucks heterozygous for RT and RT/PAIs.
Keywords: Animal cytogenetics; Meiotic segregation; Neotropical deer; Paracentric inversion; Robertsonian translocation; Sperm-FISH